Nurses’s Role to Prevent Complication in Ischemic Stroke Receiving Thrombectomy Treatment - ศรีทุมสุข วีรยุทธ; โคตะรักษ์ ชัยยุทธ; นอใส สุภลักษณ์; จูลเมตต์ พรชัย (Journal of The Royal Thai Army Nurses, 2019)
Treatment of patients with ischemic stroke through thrombectomy is another option beyond intravenous thrombolysis with recombinant tissue plasminogen activator (IV-rtPA) ipatients with large blood vessels occlusion or there are some contraindications to receiving IV-rtPA. However, such treatment methods have the potential to cause significant complications in patients such as neurological changes, intracerebral hemorrahge, or reocclusion after thrombectomy treatment including contrast-induced nephropathy etc. Nurses are important in the healthcare for taking care ischemic stroke after treating with thrombectomy. So, understanding of nursing care among pre-operative, intraoperative, and post-operative after thrombectomy treatment to prevent complications that may occur at various stages of treatment including when the patient returns to home.